Influence of self‐assembling peptide nanofibre scaffolds on retinal differentiation potential of stem/progenitor cells derived from ciliary pigment epithelial cells. (28th July 2014) - Jasty, Srilatha; Suriyanarayanan, Saranya; Krishnakumar, Subramanian
Abstract: Aim of the study was to investigate the influence of the self‐assembling peptide nanofibre scaffolds (SAPNs) on the growth, proliferation and retinal neuronal differentiation of the stem/progenitor cells (SCs) derived from the ciliary pigment epithelium (CPE) of human cadaveric eye. Here SAPNs (RADA16‐I, PM), which is well described in previous studies, commercially available and xeno‐free. The CPE cells isolated were cultured in DMEM/F12 supplemented with N2 and growth factors such as basic fibroblast growth factor and epidermal growth factor, encapsulated in the scaffolds. The entrapped SCs actively expanded and formed clone‐like clusters in the scaffolds. Many cells in the cluster were proliferating, as revealed by 5‐bromo‐2‐deoxyuridine uptake and could be maintained for up to 6 days and expressed neural progenitor markers such as β‐III tubulin, Nestin, Pax6 and Musashi1. Upon differentiation of these cells in conditioned medium, the cells exhibited retinal neuronal markers such as s‐Opsin, rhodopsin and Recoverin. The RT 2 profiler polymerase chain reaction array experiments showed selective gene expression, possibly involved in neural stem/progenitor cell adhesion and differentiation. These findings suggest the suitability of the three‐dimensional culture system for the proliferation and maintenance of CPE stem/progenitor cells (CPE‐NS) and for possible use in ex vivo studies of small molecules, drug deliveries for retinal diseases and for use in combination with directed stem/progenitor cell differentiation. and ultimately for tissue replacement therapies. Copyright © 2014 John Wiley & Sons, Ltd.